2021
DOI: 10.1038/s41598-021-01561-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic study on the complete plastomes of four officinal Ardisia species in China

Abstract: Ardisia Sw. (Primulaceae) is naturally distributed in tropical and subtropical areas. Most of them possess edible and medicinal values and are popular in clinical and daily use in China. However, ambiguous species delineation and genetic information limit the development and utilization of this genus. In this study, the chloroplast genomes of four Ardisia species, namely A. gigantifolia Stapf, A. crenata Sims, A. villosa Roxb. and A. mamillata Hance, were sequenced, annotated, and analyzed comparatively. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Additionally, the cp plays a crucial role in biochemical processes, photosynthesis, protein-coding, and the arrangement of secondary metabolic activities 11 , 12 . The cp has its genetic material separate from the nucleus and its genome, generally 120 to 170 kb in size, and encodes for 120 to 130 genes 13 . The cp genome usually has a quadripartite structure with a large single copy, a small single copy, and two inverted repeat (IRa and IRb) regions 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the cp plays a crucial role in biochemical processes, photosynthesis, protein-coding, and the arrangement of secondary metabolic activities 11 , 12 . The cp has its genetic material separate from the nucleus and its genome, generally 120 to 170 kb in size, and encodes for 120 to 130 genes 13 . The cp genome usually has a quadripartite structure with a large single copy, a small single copy, and two inverted repeat (IRa and IRb) regions 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These plastomes contain 114 unique genes, including 80 protein coding genes, 30 tRNA genes, and four rRNA genes, of which 15 genes have one intron (including rps12), two genes have two introns, and 17 genes are completely duplicated in IRs. Similar to a majority of angiosperm plastomes 27 , the rps12 in the nine plastomes is a trans-splicing gene with three exons of which two are duplicated in IRs (Table 2; Fig. 1).…”
mentioning
confidence: 99%
“…The divergent sequence of ndhF gene fragment appeared in medicinal plants of Dolomiaea (Shen et al, 2020), Rheum (Xin et al, 2022), and Crataegus (Wu et al, 2022), supporting our findings of a highly differentiated ndhF segment of the photosynthetic system gene in the cp genomes of Vincetoxicum. In this study, two highly variable regions of ndhF-rpl32 and rpl32-ccsA were found in the cp genome of V. mongolicum, which were also marked and identified as the DNA barcodes in plants such as Pterocarpus (Jiao et al, 2019), Stipa (Krawczyk et al, 2018), Ardisia (Xie et al, 2021), and Alpinia (Li et al, 2020a). Moreover, the variable loci of ndhF-rpl32 and rpl32-ccsA mostly occurred in the location of the SSC region of the Dioscorea, Digitaria, and Pennisetum species (Scarcelli et al, 2011).…”
Section: Vincetoxicum Mongolicummentioning
confidence: 50%